Iatrogenic arteriovenous fistula of the iliac artery after lumbar discectomy surgery: a systematic review of the last 18 years - Yan, Gao-Wu (Quant Imaging Med Surg, 2019)
Patients with iatrogenic iliac arteriovenous fistulas (IAVFs) after lumbar discectomy surgeries (LDSs) from our hospital and the published literature were reviewed in order to better understand this clinical phenomenon. Literature from databases about iatrogenic IAVFs after LDSs were retrieved and a patient from our hospital was reviewed with emphasis placed upon the patient’s clinical data. From 31 publications and studies of 44 individuals’ data, the study revealed L4–L5 and/or L5–S1 intervertebral space levels were mostly involved (62.0%). Most of the patients underwent computed tomography angiography (CTA) and/or digital subtraction angiography (DSA) examinations to confirm the potential diagnosis and rule out other differential diagnosis (86.4%). Most of the patients (63.6%) developed features of high output heart failure months to years after the LDSs, and the majority of them (88.6%) were treated with endovascular repairs. An iatrogenic IAVF after an LDS is a rare occurrence; however, more attention should be paid to it for the purpose of obtaining accurate diagnosis and proper treatment.